Is attending a mental process?. (31st August 2018) - Levy, Yair
Abstract : The nature of attention has been the topic of a lively research programme in psychology for over a century. But there is widespread agreement that none of the theories on offer manage to fully capture the nature of attention. Recently, philosophers have become interested in the debate again after a prolonged period of neglect. This paper contributes to the project of explaining the nature of attention. It starts off by critically examining Christopher Mole's prominent "adverbial" account of attention, which traces the failure of extant psychological theories to their assumption that attending is a kind of process. It then defends an alternative, process‐based view of the metaphysics of attention, on which attention is understood as an activity and not, as psychologists seem to implicitly assume, an accomplishment. The entrenched distinction between accomplishments and activities is shown to shed new light on the metaphysics of attention. It also provides a novel diagnosis of the empirical state of play.